Karyological analysis of two endemic Centaurea L. species from Turkey - Tasar, Neslihan; Dogan, Gulden; Evren, Harun; Kiran, Yasar (Uğur ÇAKILCIOĞLU, 2018)
In this paper, two endemic Centaurea species were investigated in terms of their chromosome numbers and karyomorphology. The chromosomal counts confirmed the results of previous reports, that the genus Centaurea has different basic chromosome numbers. Centaurea urvillei subsp. hayekiana and Centaurea saligna are diploid taxa. C. urvillei subsp. hayekiana has 2n = 20 chromosomes and a different basic chromosome number of ten, and this basic number is relatively rare for Centaurea. C. saligna has 2n = 18 chromosomes, and therefore has a basic chromosome number of nine, which is common in the genus Centaurea. Satellite was identified in the short arm of the chromosome IV. of C. saligna.
Keywords: Structural Biology; Yapısal Biyoloji